Obstetric violence: Clinical staff perceptions from a video of simulated practice. (January 2019) - Gray, Thomas; Mohan, Suruchi; Lindow, Stephen; Farrell, Tom
Abstract: Objective(s): Obstetric Violence refers to professional deficiencies in maternity care. Examples include non-dignified care, discrimination and abandonment of care. Obstetric violence has been described in both low and high resource settings. The objective of this study was to assess knowledge and attitudes towards obstetric violence in a cohort of multinational obstetric nursing/midwifery staff and obstetricians at a private maternity hospital in Qatar. Study design: An online survey for anonymous completion was sent to the hospital email accounts of obstetric nursing/midwifery staff and obstetricians at Sidra Medicine (n = 640). The survey incorporated a video showing a dramatized scenario of obstetric violence. The survey assessed the participant's demographics and knowledge of the term obstetric violence. The participants scored their perceptions on the behaviors in the video using a visual analogue scale. The participants were then asked to reflect on their own practice. Comparisons of the survey responses were made between both doctors and nursing/midiwfery staff members using student's t -test. Results: 50 obstetricians and 167 obstetric nursing/midwifery staff fully completed the survey. Fifty two percent had previously heard of the term obstetric violence, and 48% could define it correctly. 136 (63%) had witnessed obstetric violence at some point in their career. Significant differences were seen when each professional group was asked to report on the behavior of the opposite professional team as depicted in the video (p = 0.01 and p < 0.001). Doctors completing the survey were also more critical of the doctors-in-training than were the midwifery/nursing staff (p = 0.06). Obstetricians and nursing/midiwfery responders identified patient dignity, privacy and patient-centred care as the leading professional deficiencies seen in the video. Obstetricians were significantly less likely to change their perceptions of how a care team should interact with a patient compared to the obstetric nursing/midwifery group (p < 0.001). Conclusions: This questionnaire study demonstrates that the majority of staff in this cohort were aware of obstetric violence and able to identify negative behaviours in the video and then reflect on how this impacts care they provide. Further studies are needed to identify ways in which obstetric violence can be prevented in both low resource and high resource settings.